Pembelajaran Tematik: Pengembangan Media Video untuk Kemampilan Berdiskusi Siswa di Kelas V di Sekolah Dasar - Miftachur Rohmah; Sripit Widiastuti; Dwi Kameluh Agustina (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This study aims to develop thematic learning video media to improve discussion skills of fifth grade students in elementary schools. The scientific approach of the 2013 Curriculum is the basis for development, with a focus on learning methods that encourage active participation and critical thinking. Using the Research and Development (R&D) model adapted from Borg and Gall, this study went through the validation stages of material, media, and language experts. The validation results showed a feasibility percentage of 88.34% for material, 80.60% for media, and 84.45% for language, all in the